PERFORMANCE MANAGEMENT SYSTEM AT INDONESIA HIGHER EDUCATION INSTITUTION - Rizal Ramdan Padmakusumah; Adam Fatrizal; Muhammad Aghnan Nugraha; Kepin Ananda; Solahuddin Ismail (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
The intense competition among higher education institutions (HEIs) in Indonesia requires them to have a robust performance management system. This study aims to identify general performance management practices at HEIs in Indonesia, specifically at Widyatama University (UTama). This study is a qualitative study. Data credibility was tested using method triangulation. Data analysis employed content analysis and direct interpretation. The research data sources were scientific articles, secondary data, and primary data. The scientific articles were sourced from national and international journals. Secondary data consisted of strategic planning documents, quality manuals, and other related documents from several top universities in Indonesia. Primary data were collected through interviews with leaders and experts at UTama. The results of the study indicate that HEI in Indonesia and UTama already have a structured performance management system. Leaders and experts at HEI in general, and at UTama in particular, tend to choose or use the TWOS Matrix and the Balanced Scorecard (BSC) as part of their performance management system. The research results suggest that HEIs in Indonesia and UTama can create a combined performance management system using TWOS, BSC, Performance Prism, and Key Performance Indicators (KPIs) that meet both national and international criteria.